(untitled) (Faridpur Medical College Journal, 2021)
Acute myocardial infarction is one of the most important reason of death in the world. There are some established risk factors of acute myocardial infarction (AMI), but measurement of trace element like zinc can be helpful in the prevention and better management of AMI. The aim of this study was to estimate serum zinc in AMI patients. This is a case control type of study carried out in the Department of Biochemistry, Dhaka Medical College, Dhaka during the period of January 2015 to December 2015 with a total number of 100 study subjects. Acute myocardial infarction patients were selected as case (50) from coronary care unit (CCU), Department of Cardiology, Dhaka Medical College Hospital. Normal healthy individuals were selected as control (50) from the attendants of patients, relatives and doctors. Serum level of zinc was assessed for both case and control groups. The mean values of the variable were compared between them by statistical analysis using SPSS version 16. For all the statistical analysis p<0.05 was considered as significant. The mean values of serum zinc were 73.18±21.14μg/dl in cases. The mean values of serum zinc were 11.04±23.06 μg/dl in control group. Significant differences were found in mean values between case and control groups and differences were very highly significant (p-value<0.001). In AMI serum zinc levels were found to decrease in this study. Serum zinc is an important trace element act as cofactor in many biochemical reactions. Decrease level of this important trace element may contribute to pathogenesis of AMI. So with other biochemical risks parameters, routine assessment of serum zinc level is advocated, which might be helpful for prevention and better management of AMI. Faridpur Med. Coll. J. 2020;15(2): 92-94